2013
DOI: 10.4068/cmj.2013.49.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Cyst Presenting as Acute Pancreatitis: Report of a Case

Abstract: We report the first case of hypercalcemia-induced acute pancreatitis caused by a functioning parathyroid cyst in a 67-year-old man. Laboratory investigation revealed increased serum amylase and lipase, increased serum ionized calcium and parathyroid hormone (PTH) levels, and decreased serum phosphate, indicating pancreatitis and primary hyperparathyroidism (PHPT). Abdominal computed tomography (CT) revealed mild swelling of the pancreatic head with peri-pancreatic fat infiltration and fluid collection around t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In agreement with previous studies, cystic parathyroid adenomas in the present cohort were found to be associated with high serum levels of iPTH and calcium [ 5 , 21 ]. Additionally, a higher incidence of hypercalcemic crisis was observed in patients with cystic adenomas than in patients with solid adenomas.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies, cystic parathyroid adenomas in the present cohort were found to be associated with high serum levels of iPTH and calcium [ 5 , 21 ]. Additionally, a higher incidence of hypercalcemic crisis was observed in patients with cystic adenomas than in patients with solid adenomas.…”
Section: Discussionsupporting
confidence: 93%